Ribosomal DNA analysis of a harmful algal bloom (HAB) species, Pyrodinium bahamense var. Compressum and its associated marine microbes - Chin, Grace Joy Wei Lie (2008)
Harmful algal blooms in Sabah occur mostly in the coastal waters of west Sabah, where one of the causative organisms is the toxin-producing dinoflagellate, Pyrodinium bahamense var. compressum. Pyrodinium cells were isolated from four locations, namely, Sepanggar Bay, Gaya Bay, Kinarut and Kota Belud and cultured in f/2 medium. Ribosomal DNA fingerprinting of the five Pyrodinium isolates was done by means of Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) analysis of the 18S ribosomal DNA. A total of eight restriction enzymes, Haan, DpnII, A/IA, RsaI, BsaJI, 8s8-JI, Bsd.JI and Ta(fl., were used to determine the genetic relationship of the five isolates. The RFLP analysis yielded similar restriction patterns among the five isolates. The 185 rDNA sequences of all the Pyrodinium isolates were also obtained (Accession numbers: DQ500119 to DQS00123). The size of sequences ranged from between 1,580 to 1,544 base pair (bp ). Based on the sequence data, a Pyrodinium-specitic primer, CWL1R, was designed. To confirm the specificity of this DNA primer, a group of dinoflage11ates, such as Cochlodinium po/ykrikoldes, Gymnodinium catenatum, Amphldinium sp., Gambierdiscus sp., Prorocentrum micans, Prorocentrum lima, Ostreopsis sp., Coolia sp., Alexandrium minutum, Alexandrium tamarense, Crypthecodinium cohnii, Gonyaulax cochlea, Lingulodinium polyedra, Peridinium sp. and Pyrocystis /unula were se'lected for 185 rDNA amplification. The results showed that this primer could only amplify the rDNA of Pyrodinium. Therefore, the primer CWL1R has a great potential to be developed as a PCR-based DNA probe for the identification of Pyrodlnium bahamense var. compressum. Sensitivity ana1ysis was also conducted on Pyrodinium cutture, G1. Based on the results obtained, PCR could amplify DNA template even after the DNA was serially diluted 11 times, where the DNA concentration was 1.6 x 10-9 ng/μI, which correspond to cell concentration of 2.5 x 10-5 ce11s/l. However, the calculated DNA template concentration for dilution factor 10-11 was too low for PCR amplification. This is maybe due to cross-contamination between samples during the dilution process or error in obtaining the DNA concentration in the first undi1uted samp1e. Besides that, ribosomal DNA-based restriction enzyme analysis for the identification of bacteria associated with Pyrodinium was also conducted. A total of 16 marine bacterial isolates were successfully obtained from clonal cultures of Pyrodinium. The study revealed that al1 bacterial isolates were Gram negative except for two isolates, which were Gram positive. Restriction enzyme analysis yielded eight different ribotypes. Toe 16S rDNA sequences of bacteria associated with Pyrodinium were obtained (Accession numbers: EF688604 to EF688619). Based on the sequencing results of 16S rDNA, the genetic diversity of the extraceflu1ar microbes associated with Pyrodinium was limited to the Phyla Proteobacteria and Actinobacteria. The majority of bacteria were Alcanivorax sp. and Hyphomonas sp., whereas Kocuria sp., Nesterenkonia sp., Alteromonas sp., Roseobacter sp., Xanthomonas sp., and Aclnetobacter sp. were identified as minor isolates. These resu1ts showed that the dinoflagellate, Pyrodlnium bahamense var. compressum might live, symbiotically or not, with various bacteria in the natural environment.